National Accounts Statistics: Main Aggregates and Detailed Tables 2023 - United Nations Department of Economic; Social Affairs (United Nations, 2024)
This is the sixty-fifth issue of National Accounts Statistics: Main Aggregates and Detailed Tables, showing detailed national accounts estimates for 210 countries and areas for the reporting years 2012 to 2023. The national data for each country and area are presented in separate chapters using uniform table headings and classifications recommended in the United Nations System of National Accounts (SNA). A summary of the conceptual framework of the SNA and definitions of important terms are also included in this publication. Other statistical information covered includes gross domestic product, national income, savings, private and government consumption, and transactions of institutional sectors.